Fabrication and Characterization of Dye-doped Polymer Optical Fiber - Chiad, Baha T. (University of Thi-Qar Journal of Science, 2014)
This paper is concerned with the design a special perform drawing system for fabricated Step Index-Single Mode Polymer Optical Fiber (SI-SM POF). The POF has been fabricated by this device based on a highly crosslinked poly methyl methacrylate (PMMA) as a core material and a dye-doped PMMA cladding layer. The refractive indices of the core material and the cladding are 1.49 and 1.35, respectively. The physical and optical properties of POF have been studied, which fabricated at different diameters. Laser light (633 nm) was coupled in to the POF using standard prism coupling techniques. From the morphological analysis of the POF it has been shown that the homogenous and the viscidity of the core and cladding is suitable. In additional to the core is completely in the center of the POF.